An improved continuous sterilization process for palm oil milling process - Ahmadun, Fakhru'l-Razi; Ismail, Mohd Halim Shah; Choong, Thomas Shean Yaw (2009)

(untitled)
An improved continuous sterilization process on fresh oil palm fruit bunches (FFB) comprising crushing the fresh oil palm fruit bunches, heating the crushed oil palm fruit bunches and transferring the crushed oil fruit bunches into a sterilizer vessel by a conveyor (7). The improved continuous sterilization process has allowed the sterilizer vessel to be operated at low system pressure in order to overcome the poor system management in the palm oil mill. This continuous sterilization vessel have excellent capability to maintain the temperature as well as the pressure of the steam inside the vessel during the sterilization process. Introducing a new pre-treatment step before the sterilizer process further reduces the stem required in the sterilizer vessel. As a result of extensive studies, the continuous sterilization process is found to be suitable for implementation in palm oil mill and is also capable of improving the continuous process of sterilizing the Fresh Oil Palm Fruit Bunches (FFB).